Exploring the Impact of Specially Trained Dogs on the Court Experiences of Sexual Offence Survivors in England and Wales: an Exploratory Case Study - Spruin, Elizabeth (European journal on criminal policy and research, 2020)
The current research explored the impact of specially trained dogs on the experiences of sexual offence survivors in an English and Welsh court environment. In total, five cases of survivors of sexual offences were provided with a specially trained dog during court proceedings. In each case, data were collected from several sources, including interviews, observations and various documentation. Using a thorough multiple-case-study design, data were analysed both within and across all cases to identify any individual and thematic patterns. The within-case analysis found that the dog aided survivors in becoming calmer and less anxious. The across-case analysis indicated five reoccurring themes pertaining to the survivor: (1) impact of court context, (2) emotional impact of dog on survivors, (3) physical impact of dog on survivors, (4) change in anchoring due to presence of the dog, and (5) the uniqueness of a dog as a companion. The findings also highlighted important considerations when utilising such services to support survivors at court. Overall, these results identified a large number of benefits not only to the survivors, but also their families and other supporting individuals, providing the first global evaluation of such service for survivors of sexual offence, which should aid in considering the introduction of this service internationally. It is thus recommended that the criminal justice system in England and Wales further explore the use of this service.